واقع ممارسة إدارة المواهب البشرية وأثرها في إدارة التغيير وتحقيق التمييز في جامعة صحار بسلطنة عمان - علوي ، خالد علي خلفان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The purpose of this research is to diagnose the reality of talent management practice at the Sohar University in terms of attracting talents, managing their performance, developing and maintain them and determining the impact of talent management practice with all it dimensions in change management in administrative, structural, technological and behavioral fields at Sohar University. The research adopted the descriptive analytical approach and the questionnaire used as a tool to collect data. There were samples collected from (217) participants included in the research from both administrators and supervisors for the year 2018 - 2019. The statistical methods used in analyzing data included: Cronbach's alpha, iterations, Arithmetic means, Percentages and Standard deviation through the Statistical Package Program (SPSS). The results showed that the reality of practicing talent management at Sohar University (attracting talented people, managing their performance, developing and maintaining them) was indefinite as there is no autonomous administration within the university and all the proceedings within the human resources management at the university. Neither is there an effective talent management practice in the change management process. Therefore, providing a clear strategy to talent management is urgently needed to facilitate a more competitive nature of the institution in an ever competitive world of quality higher educational service.